Contextual affect analysis: a system for verification of emotion appropriateness supported with Contextual Valence Shifters. (25th February 2010) - Ptaszynski, Michal; Dybala, Pawel; Shi, Wenhan; Rzepka, Rafal; , Kenji Araki
This paper presents a novel method for estimating speaker's affective states based on two contextual features: valence shifters and appropriateness. Firstly, a system for affect analysis is used to recognise specific types of emotions. We improve the baseline system with the analysis of Contextual Valence Shifters (CVS), which determine the semantic orientation of emotive expressions. Secondly, a web mining technique is used to verify the appropriateness of the recognised emotions for the particular context. Verification of contextual appropriateness of emotions is the next step towards implementation of Emotional Intelligence Framework in machines. The proposed method is evaluated using two conversational agents.